Protection of rare and protected species of flora in large petrochemical projects - Popova, Elena I.; Kozlov, Stanislav I. (Acta Biologica Sibirica, 2022)
The paper presents a comprehensive assessment of vegetation biodiversity at the construction site of the ZapSibNeftekhim production complex in the city of Tobolsk, Tyumen Region, Russia. In this paper, we (1) study the biogenic and salt composition of the soil; (2) label the revealed samples, (3) record the geographical coordinates; (4) use the method of translocation (transfer) of the rare and endangered flora representatives found at the construction site of the ZapSibNeftekhim and the associated facilities, as well as the removal of such species from the original habitat, and their transportation to new habitats. In total, 149 individuals of 13 flora species were transferred during the work: (1) Malaxis monophyllos L., (2) Listera ovata (L.) R. Br., (3) Dactylorhiza maculata (L.) Soo, (4) Allium microdictyon Prokh., (5) Centaurea phrygia L., (6) Phegopteris connectilis (Michx.) Watt, (7) Polyporus badius (Pers.) Schwein., (8) Iris sibirica L., (9) Daphne mezereum L., (10) Lilium pilosiusculum (Freyn) Miscz., (11) Cinna latifolia (Trev.) Griseb., (12) Platant herabifolia (L.) Rich., (13) Heterodermia japonica (M.Sato) Swinscow et Krog. In addition, we took into account all the biological characteristics of the transferred flora species and their environmental requirements during monitoring activities. Adaptation of almost all translocated specimens was successful. Research in this area contributes to a deeper understanding of the processes of anthropogenic transformation of floristic complexes and should be the basis for environmental monitoring of disturbed habitats. These studies allow approaching the solution of problems of rational use, conservation and restoration of life-support resources in ecosystems, integrity, productivity, and biodiversity of biological resources.